ANALISIS PENYEBAB KEGAGALAN MENDIRIKAN USAHA BARU PADA PARA LULUSAN PROGRAM WIRAUSAHA BARU JAWA BARAT KELAS IDE BISNIS - Srihadiastuti, Rida; Hidayatullah, Deden Syarif (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2018)
Wirausaha Baru Jawa Barat Program (WUB Jabar Program) which organized by Badiklatkop Bandung, is an entrepreneurship training in 3 choices of business field, those are food-beverage, convection, and salon. Participants are divided into Ide Bisnis class, Start-up class, or Growth class. Ide Bisnis Class is for participants who do not have a business, or already have a business but not yet reached the age of 1 year. Through a survey of 237 Ide Bisnis class graduates, there were 21 people who failed in establishing their new business after participated in the program. This research aims to determine the factors that caused failure. The qualitative descriptive method used in this research. Data collection techniques with an observation of program WUB Jabar, and interviews with 7 graduates who experienced business failure, also to 5 graduates whose business is still continuing. Data analysis techniques with Miles and Huberman models. The results of this research explained that the main factor causing graduates new business failure is the barrier on capital because barriers on capital causing barriers on other factors. And capital factor is also the most difficult barrier to be solved by the graduates who do not experience the business failure